Age-related differences in white matter integrity and cognitive function are related to APOE status - Ryan, Lee (2010)
While an extensive literature is now available on age-related differences in white matter integrity measured by diffusion MRI, relatively little is known about the relationships between diffusion and cognitive functions in older adults. Even less is known about whether these relationships are influenced by the apolipoprotein (APOE) ε4 allele, despite growing evidence that ε4 increases cognitive impairment in older adults. The purpose of the present study was to examine these relationships in a group of community-dwelling cognitively normal older adults. Data were obtained from a sample of 126 individuals (ages 52–92) that included 32 ε4 heterozygotes, 6 ε4 homozygotes, and 88 non-carriers. Two measures of diffusion, the apparent diffusion coefficient (ADC) and fractional anisotropy (FA), were obtained from six brain regions – frontal white matter, lateral parietal white matter, the centrum semiovale, the genu and splenium of the corpus callosum, and the temporal stem white matter – and were used to predict composite scores of cognitive function in two domains, executive function and memory function. Results indicated that ADC and FA differed with increasing age in all six brain regions, and these differences were significantly greater for ε4 carriers compared to noncarriers. Importantly, after controlling for age, diffusion measures predicted cognitive function in a region-specific way that was also influenced by ε4 status. Regardless of APOE status, frontal ADC and FA independently predicted executive function scores for all participants, while temporal lobe ADC additionally predicted executive function for ε4 carriers, but not noncarriers. Memory scores were predicted by temporal lobe ADC but not frontal diffusion for all participants, and this relationship was significantly stronger in ε4 carriers compared to noncarriers. Taken together, age and temporal lobe ADC accounted for a striking 53% of the variance in memory scores within the ε4 carrier group. The results provide further evidence that APOE ε4 has a significant impact on the trajectory of age-related cognitive functioning in older adults. Possible mechanisms are discussed that could account for the associations between ε4, diffusion, and cognitive function, including the influence of ε4 on neural repair, oxidative stress, and the health of myelin-producing oligodendroglia.